The Effect of THM (Traditional Herbal Medicine) On Reducing Blood Sugar Levels in Type 2 Diabetes Mellitus Patients in Indonesia: A Sytematic Review and Meta-Analysis - Ardini Syahrini; Arrafi Insani (Jurnal Kebidanan dan Kesehatan Tradisional, 2026)
Background: Diabetes is a global health issue that currently receives widespread attention. Indonesia, a tropical archipelagic nation and a hotspot for biodiversity, offers a rich array of natural resources, making the use of herbal plants or traditional medicine a popular treatment option among the public. This study aims to conduct a systematic review and meta-analysis regarding the effect of THM (traditional herbal medicine) on blood sugar reduction in patients with type 2 diabetes. Methods: This study aims to conduct a systematic review and meta-analysis regarding the effect of THM (traditional herbal medicine) on blood sugar reduction in patients with type 2 diabetes. This study was conducted using a systematic review method followed by meta-analysis, which is a statistical technique to quantitatively combine the findings from previous studies. Results: The review found that the intervention of boiling leaves of bay leaf (PMD: -39.09 mg/dL), moringa leaves (PMD: -50.98 mg/dL), and ginger (PMD: -53.45 mg/dL) significantly influenced blood sugar reduction in patients with type 2 diabetes (p-value < 0.001). Conclusion: The analysis shows a significant reduction in blood sugar in type 2 diabetes patients after the administration of ginger, bay leaf, and moringa leaf decoctions, with a decrease of 5.83 mg/dL per day. Health professionals can provide appropriate education on their use alongside standard diabetes management.